2017
DOI: 10.1080/03055698.2017.1347489
|View full text |Cite
|
Sign up to set email alerts
|

Collective self-efficacy expectations in Co-teaching teams – what are the influencing factors?

Abstract: Scholars have studied collective teacher efficacy mainly at the school level. The present study also focuses on collective teacher efficacy expectations, but it emphasises the collaborative teaching of two teachers working together in one classroom. This study investigates personal, contextual, and systemic factors (e.g. experience, gender, class composition, pleasure with Co-teaching and its standards, knowledge about specific Co-teaching skills, the way how the team partner was chosen, etc.) that may influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…Previous studies have shown that co‐teaching increases teachers’ job satisfaction and well‐being (Sirkko et al, 2018). Students’ support needs are better met when there are more teachers in the classroom (Krammer et al, 2018). Implementing co‐teaching can reduce segregation (Strogilos et al, 2016), promote inclusion, improve students’ socio‐emotional and interaction skills (Friend et al, 2010; Strogilos & Stefanidis, 2015) and reduce students’ challenging behaviour (Strogilos & Avramidis, 2016; Botha & Kourkotas, 2016).…”
Section: Teachers’ Views On the Benefits And Challenges Of Co‐teachingmentioning
confidence: 99%
“…Previous studies have shown that co‐teaching increases teachers’ job satisfaction and well‐being (Sirkko et al, 2018). Students’ support needs are better met when there are more teachers in the classroom (Krammer et al, 2018). Implementing co‐teaching can reduce segregation (Strogilos et al, 2016), promote inclusion, improve students’ socio‐emotional and interaction skills (Friend et al, 2010; Strogilos & Stefanidis, 2015) and reduce students’ challenging behaviour (Strogilos & Avramidis, 2016; Botha & Kourkotas, 2016).…”
Section: Teachers’ Views On the Benefits And Challenges Of Co‐teachingmentioning
confidence: 99%
“…It is important to note, however, that personal characteristics, attitudes and perceptions of the team members are considered as more important for team quality than structural characteristics (Biemann and Weckmüller 2012;Honingh and Hooge 2014;Krammer et al 2017). These personal characteristics refer to a considerable number of prerequisites which must be fulfilled in order to provide good quality joint teaching.…”
Section: General Frameworkmentioning
confidence: 99%
“…Instead of referring certain pupils to an intensive special education service outside of the regular classroom, the SET brings his or her competence into the regular classroom (Friend et al, 2010;King-Sears, Jenkins, & Brawand, 2018;Scruggs & Mastropieri, 2017). Another central benefit conferred by co-teaching that supports inclusive education is the increased teacher-pupil ratio, which improves teachers' abilities to differentiate between students and meet individual needs without excluding pupils (Friend et al, 2010;Krammer, Gastner, Paleczek, Gasteiger-Klicpera, & Rossman, 2018).…”
Section: Co-teaching As An Inclusive Teaching Strategy: the Benefits And Challengesmentioning
confidence: 99%